PENILAIAN MUTU FISIK BUKU AJAR DI PRODI TEKNIK GRAFIKA DITINJAU DARI ASPEK KEGRAFIKAAN - Sinambela, Yusnia; Juwairiah; Fitri Evita (Politeknik Negeri Bengkalis, 2023)
There are still many textbooks circulating in the market that do not consider the physical quality of books or graphical aspects. Even though this aspect is very influential on students' interest in reading or students' seriousness in learning. There are several things that need to be considered to produce a good physical quality of the book. These things include front cover components, layout, illustrations, formats, paper, typography, print quality, volume quality and all of that is based on knowledge and standardization that has been determined. Textbooks used in the Graphic Engineering study program need to be assessed for their physical quality whether they have considered graphical aspects. The method used is to use observation and be guided by the specifications/standards that have been determined. The results of the assessment were that the physical quality of the books used in the Graphic Engineering Study Program had met the specified specifications/standards and the textbook that had the highest total weighted score was the Industrial Psychology book total value of 76 and the lowest was the production system textbook with a weighted total value of 65.20. Keywords: Quality, Textbooks, Graphics